Cultura organizacional como apoio à institucionalização de processos de software - FERNANDES, Patrícia Gomes (2010)
Many organizations are applying efforts to improve their software processes, in face of the premisse that states that the quality of the processes used to develop and maintain software has a major influence over the products generated. These efforts are typicaly in the form of software process improvement (SPI) initiatives, with the general objetive defining and/or improving software processes, as well as institutionalizing them. Nevertheless, once it involves changes in the way of work of organizations, SPI provokes changes in organizational culture, and is impacted by this culture. This is reflected in SPI literature, that presents organizational culture as a critical success factor in SPI implementation. The focus of this research is the investigation of the correlation between organizational culture and the effectiveness of SPI initiatives. In order to do this, two fundamental questions were considered: (a) how the culture of an organization can influence the degree of institutionalization of a defined/improved software process, and (b) what can be done to increase the degree of institutionalization of a defined/improved software process, once this institutionalization involves a cultural change. To accomplish this, a case study was conducted in two software organizations (where only one of them institutionalized its software process) with the purpose of analysing how their cultural profiles may have influenced in these different outcomes. It was also conducted a search to identify recommendations for cultural change in Organizational Culture literature. The application of these recommendations was evaluated in a comparative way in both organizations. Additionaly, a survey with SPI implementors was also made, in order to identify the degree of application of these recommendations in the organizations they have worked. With this research, cultural elements that may have relations whit software process institutionalization were identified, as well as recommendations that can derive actions to modify the elements that are considered resistance factor to the adoption of software processes defined/improved in SPI initiatives.